A study of serum electrolyte imbalances and its impact in children of 4 months to 5 years of age group presenting with acute gastroenteritis - Joseph, Dibin; Keithellakpam, Sunilbala (International Journal of Contemporary Pediatrics, 2023)
Background: Fluid and electrolyte derangement are the immediate causes that increases the mortality in diarrhea. The present study was carried out among children of 4 months to 5 years with dehydration due to acute diarrhea to determine the serum electrolyte profile. Methods: A hospital based cross sectional study was carried out in department of pediatrics, RIMS during a period of two years (sept 2019-Aug 2021). Results: A total of 195 patients of 4 months to 5 years of age group presented with acute gastroenteritis were included in the study, among them hyponatreamia was the most frequent electrolyte abnormality noted (37.4%). Most (65.5%) of hyponatremic patients in our study took dilute ORS whereas majority (64.2%) of patients who took appropriate ORS had normal serum sodium levels. Frequency and duration of diarrhea, dehydration status and inappropriate ORS were significant risk factors for serum electrolyte and acid base imbalances. Conclusions: Electrolyte abnormalities were significantly associated with frequency and duration of diarrhea, dehydration status and inappropriate ORS administration. Hence, timely recognition and management of electrolyte abnormalities and appropriate ORS administration improves outcome in acute gastroenteritis related dehydration in children.